Analysis of the Dramatic Structure of the Play "Gunung Sari Kembar" in the Wayang Topeng Jatiduwur Performance in Jombang Regency: Analysis of the Dramatic Structure of the Play "Gunung Sari Kembar" in the Wayang Topeng Jatiduwur Performance in Jombang Regency - iswanda, vignadia aurelita; S.Sn., M.Si, Dr. Indar Sabri (APRON Jurnal Pemikiran Seni Pertunjukan, 2024)
This study aims to analyze the dramatic structure in the play Gunung Sari Kembar performed in the Wayang Topeng Jatiduwur in Jombang Regency. This analysis uses a qualitative descriptive approach to delve into the dramatic elements present in the play. The research finds that the dramatic structure of the play Gunung Sari Kembar consists of several key stages, including introduction, conflict, climax, and resolution. Each stage plays a crucial role in building a cohesive and engaging storyline. The analysis shows that the use of dramatic elements in this play effectively portrays the story and characters, maintaining the audience's attention throughout the performance. Keywords: Dramatic Structure, Play, Gunung Sari Kembar, Wayang Topeng Jatiduwur, Qualitative Analysis.